Personal Attitude, Subjective Norms and Self-efficacy as Predictors of Entrepreneurial Intentions: The Moderating Effect of Entrepreneurship Education - Paudel, Prakash (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to examine how self-efficacy, subjective norms, and the predictive value of attitude affect the entrepreneurial intentions of graduate (master’s) management students in the Butwal Sub-metropolitan area. Methods: Convenience sampling was used to systematically gather data, with a focus on 253 Butwal Sub-metropolitan master’s students studying management. A precise seven-point Likert scale was used in the study’s adopted questionnaire. Similar to this, a descriptive and causal comparison study approach was employed, complemented by a variety of statistical measures that were carefully selected to enable reliable data analysis, including Mean, Standard Deviation, Correlation, and Regression. Results: The results depict that the most significant influencing factor is personal attitude. People are more inclined to take the chance and launch their own company if they have a positive outlook on entrepreneurship and feel encouraged by their network. Conclusion: This study concludes that academic intuitions should facilitate training and workshop among their students to develop positive attitudes so that they can be encouraged to set up their own entrepreneurial venture. Likewise, the social community should provide emotional support among students to develop entrepreneurial intention.